2011
DOI: 10.1371/journal.pone.0028621
|View full text |Cite
|
Sign up to set email alerts
|

Time Estimation Predicts Mathematical Intelligence

Abstract: BackgroundPerforming mental subtractions affects time (duration) estimates, and making time estimates disrupts mental subtractions. This interaction has been attributed to the concurrent involvement of time estimation and arithmetic with general intelligence and working memory. Given the extant evidence of a relationship between time and number, here we test the stronger hypothesis that time estimation correlates specifically with mathematical intelligence, and not with general intelligence or working-memory c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 43 publications
(57 reference statements)
2
21
0
Order By: Relevance
“…Similarly, Droit-Volet, Clément, and Fayol (2003) showed that number interfered with temporal performance in 5-year-old children, indicating that the processing of time and number may already be interrelated at preschool age (see also Droit-Volet, Clément, & Fayol, 2008). Furthermore, other studies performed in normal populations found relationships between time processing and calculation skills (Skagerlund & Träff, 2016), as well as general mathematical intelligence (Kramer, Bressan, & Grassi, 2011). Finally, a recent study found a strong association in primary school children between conventional time knowledge, measured with a questionnaire, and numerical skills, such as number facts, number line estimation, and number comparisons (Labrell, Mikaeloff, Perdry, & Dellatolas, 2016).…”
Section: Introductionmentioning
confidence: 88%
“…Similarly, Droit-Volet, Clément, and Fayol (2003) showed that number interfered with temporal performance in 5-year-old children, indicating that the processing of time and number may already be interrelated at preschool age (see also Droit-Volet, Clément, & Fayol, 2008). Furthermore, other studies performed in normal populations found relationships between time processing and calculation skills (Skagerlund & Träff, 2016), as well as general mathematical intelligence (Kramer, Bressan, & Grassi, 2011). Finally, a recent study found a strong association in primary school children between conventional time knowledge, measured with a questionnaire, and numerical skills, such as number facts, number line estimation, and number comparisons (Labrell, Mikaeloff, Perdry, & Dellatolas, 2016).…”
Section: Introductionmentioning
confidence: 88%
“…The IBs task is based on the Tactile Estimation Task (TET) for spatial recognition, but the protocol is adapted to temporal estimation (Kramer et al, 2011 ), thus providing a simple and non-invasive procedure to assess the degree of estimation of duration of the interoceptive stimulus. The task consists in delivering interoceptive brush strokes to subject’s left volar forearm, and successively asking for verbal time estimation (VET) of the time passed.…”
Section: Methodsmentioning
confidence: 99%
“…Temporal acuity There is also a relation between temporal acuity and formal math (e.g., Odic et al, 2016;Skagerlund & Träff, 2016); however, the reasoning for this relation is less obvious. Some have argued that a unique relation between temporal and spatial abilities may mediate the relation between time and math (Kramer, Bressan, & Grassi, 2011), whereas others have suggested that the ability to manipulate ordered magnitude, which is important for both numerical and temporal processing, may be key in understanding the relation between temporal processing and mathematics (Skagerlund & Träff, 2016).…”
Section: Relation To Formal Learningmentioning
confidence: 99%